Modern slavery in global context: human rights, law, and society - Faulkner, Elizabeth (Bristol University Press, 2024)
This collection brings together academics from a range of disciplines to examine modern slavery. Providing a platform to critique the legal, ideological and political responses to the issue, experts interrogate the construct of modern slavery and the anti-trafficking discourse which have dominated contemporary responses to exploitation.